2020
DOI: 10.1007/s10495-020-01648-8
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular lactate-to-pyruvate ratio modulates the sensitivity to oxidative stress-induced apoptosis via the cytosolic NADH/NAD+ redox state

Abstract: The advantages of the Warburg effect on tumor growth and progression are well recognized. However, the relevance of the Warburg effect for the inherent resistance to apoptosis of cancer cells has received much less attention. Here, we show here that the Warburg effect modulates the extracellular lactate-to-pyruvate ratio, which profoundly regulates the sensitivity towards apoptosis induced by oxidative stress in several cell lines. To induce oxidative stress, we used the rapid apoptosis inducer Raptinal. We ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…Cell proliferation and apoptosis are fundamental for normal cell growth and development. Abnormal cell growth is a key marker for cancer (Shi et al, 2020a;Go et al, 2021;. It has been shown that microRNA-1914 could increase the effect of DUXAP10 on cell proliferation and apoptosis through activation of the GPR39-mediated PI3K/AKT/mTOR pathway in HCC Hep3B and MHCC-97L (Sun et al, 2019) cells (Figure 2).…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Cell proliferation and apoptosis are fundamental for normal cell growth and development. Abnormal cell growth is a key marker for cancer (Shi et al, 2020a;Go et al, 2021;. It has been shown that microRNA-1914 could increase the effect of DUXAP10 on cell proliferation and apoptosis through activation of the GPR39-mediated PI3K/AKT/mTOR pathway in HCC Hep3B and MHCC-97L (Sun et al, 2019) cells (Figure 2).…”
Section: Cell Proliferation and Apoptosismentioning
confidence: 99%
“…Even this role in autophagy might have a hormetic cause, as the same l -lactate has an inhibitory action on autophagy when cells have lost their stress responsivity, such as in tumors (Matsuo et al 2019 ). Again, in this perspective, l -lactate should exert a fundamental regulatory activity even on apoptosis (Go et al 2021 ). At least on HepG2 cell lines, the increase in the extracellular lactate-to-pyruvate ratio has the ability to reduce the cytosol NADH/NAD + redox state and inhibiting stress-induced apoptosis (Go et al 2021 ).…”
Section: Insights About L -Lactate As a Signaling ...mentioning
confidence: 99%
“…Again, in this perspective, l -lactate should exert a fundamental regulatory activity even on apoptosis (Go et al 2021 ). At least on HepG2 cell lines, the increase in the extracellular lactate-to-pyruvate ratio has the ability to reduce the cytosol NADH/NAD + redox state and inhibiting stress-induced apoptosis (Go et al 2021 ). Moreover, high extracellular l -lactate inhibits the intrinsic apoptotic pathway by reducing the activation of JNK and Bax (Go et al 2021 ).…”
Section: Insights About L -Lactate As a Signaling ...mentioning
confidence: 99%
“…Apoptosis is a type of programed cell death that has been implicated in the development and occurrence of cancers (159)(160)(161)(162)(163). FOXD3-AS1 was demonstrated to suppress the apoptosis of NSCLC A549 and H1229 cells through functioning as a ceRNA for miR-135a-5p and elevating CDK6 expression (24).…”
Section: Cell Apoptosismentioning
confidence: 99%